Phytopharmacasia Stimuno Syrup as a Traditional Medicine - Nastiti, Kunti; Gusnianti, Elva; Azzahra, Fatimah; Alfisah, Firda; Saniah, Husnus; Khatimah, Indah Husnul (Universitas Ibn Khaldun Bogor, 2024)
This study aims to evaluate the efficacy and safety of Stimuno Syrup as an immunomodulator in improving the immune system. A descriptive-analytical approach is used to collect information on the composition, active ingredients, and efficacy claims of Stimuno Syrup from various reliable sources, including scientific literature and information from the Food and Drug Supervisory Agency (BPOM). The composition analysis of Stimuno Syrup includes the identification of the main active ingredients, the content of the active substances, as well as the evaluation of the product packaging and label. Furthermore, empirical data from preclinical and clinical studies were evaluated to provide a comprehensive picture of the efficacy and safety of Stimuno Syrup. The results of this study are expected to provide a clearer understanding of the potential of traditional medicine in the modern context as well as provide stronger scientific support for the use of Stimuno Syrup as an alternative in maintaining health and increasing immunity.